Draft Genome Sequences of Macrococcus caseolyticus, Macrococcus canis, Macrococcus bohemicus, and Macrococcus goetzii. - Mazhar S; Altermann E; Hill C; McAuliffe O (American Society for Microbiology, 2019)
Here, we present the draft genome sequences of 14 strains of 4 species of the genus Macrococcus These strains were isolated from bovine milk and tongue samples obtained during a screening program.